Brazil, South Africa and the international recognition of LGBT Rights: Proposals for a comparative research agenda - Klein, Magno (Cadernos de Gênero e Diversidade, 2021)
The paper proposes a comparative analysis of the LGBT rights agenda in the foreign policies of Brazil and South Africa. In both countries, authoritarian regimes gave way to democratic orders in the late 1980s / 1990s, which saw the formation of vocal LGBT groups and constitutional recognition of some rights. Both Brazil and South Africa have become leading voices in the global South supporting LGBT rights, in particular at the UN Human Rights Council. Brazil was the first country to propose an international normative text dedicated exclusively to LGBT rights, maintaining a long-term leadership position regarding the promotion of norms in this agenda at the global and regional levels. South Africa's position has been erratic. It was very active in the 90s, but regressive and silent in the 2000s. Since 2011, however, the country has again become a protagonist in relation to sexual issues, as illustrated by a major step in the recent presentation of a resolution on sexual orientation and gender identity. This research agenda is still little explored, especially from a comparative perspective of the political contexts of emerging democratic countries. In the end, the paper proposes six key questions for a comparative analysis of the performance of the two governments in this agenda, taking special account of the growing conservatism in both societies, which in the Brazilian case is marked by the election of President Jair Bolsonaro.